The Impact Of A Structured Counseling Technique By Pharmacist On Knowledge, Satisfaction, Quality Of Life, Adherence And Clinical Outcomes Among Asthma Patients At King Saud Hospital, Saudi Arabia - Naif G, Alotaiby Meshal (2017)
The pharmacist is expected to play a vital role in chronic disease management. The present study aimed at developing an educational tool (booklet) and described a pharmacist--mediated structured medication counseling for asthmatic patients. It also determined the impact of pharmacist intervention on asthma patient’s knowledge, satisfaction, medication adherence, quality of life, clinical outcomes (peak expiratory flow rate, PEFR), and drug therapy-related problems (DTRPs). A randomized controlled trial compared the conventional routine counseling [control (n = 38)] with structured medication counseling provided by pharmacist [intervention (n = 37)] at the Outpatient Department of the Chest Clinic at King Saud Hospital, Qassim, Saudi Arabia.